Vowed to community or ordained to mission? Aspects of separation and integration in the Lutheran Deaconess Institute Neuendettelsau, Bavaria - Böttcher, J (2015)
This study offers an overdue exploration of the early years of the deaconess community in Neuendettelsau from a gender perspective. Drawing on rich archival material, it focuses on the process of the formation of a distinctive collective identity. Central to this study is the assumption, drawn from the social sciences, that collective identity is a social construction which requires the participation of the whole group through identification and which is consolidated by developing specific rituals, symbols, codes and normative texts, which facilitate integration, and by constructing external boundaries, which separate from the world and wider church. The centrifugal forces which came into play when deaconesses were sent out in isolation were counterbalanced by a communal life which offered forms of participation and identification for the individual members and which consolidated their sense of belonging. The first chapter introduces the methodology. Chapter Two explores the social, cultural and theological context of the foundation of the Deaconess Institute, and offers a brief outline of the institution's historical development. The third chapter offers an in-depth analysis of the initiation ceremony as a rite which both admitted into the community and conferred an ecclesiastical office. Chapter Four analyses formative and normative texts that shed light on the community's norms, values, and expectations. In the fifth chapter, non-literary means of consolidating and affirming the deaconesses' collective identity are explored. This study concludes that the process of the emergence of a specific deaconess culture was pervaded by bourgeois norms, values, patterns of behaviour and notions about gender roles which measured out the women's radius of action and were at times difficult to reconcile with the deaconess profession.